Physical activity, night eating, and mood state profiles of athletes during the COVID-19 pandemic - Turgut, M.; Soylu, Y.; Metin, S. N. (Progress in Nutrition, 2020)
Objectives: The aim of this study was to examine the effect of COVID-19 Pandemic physical activity, night eating, and mood in athletes.